Continuous milking of dairy cows disrupts timing of peak IgG concentration appearance in mammary secretions. Issue 4 (November 2014) - Baumrucker, Craig R; Zbinden, Rahel S; van Dorland, H Anette; Remmelink, Gerrit J; Kemp, Bas; van Knegsel, Ariette T M; Bruckmaier, Rupert M
<x content-type="archive" xml:space="preserve">Abstract</x> The length of the dry period in commercial dairy production is under close scrutiny. While the main concern is the composition and volume of milk produced, the evaluation of colostrum quality under these new paradigms has suggested a decline in IgG concentrations, while some reports indicate no change. Colostrum quality has been defined as an adequate concentration (>50 mg/ml) of immunoglobulin in the secretions to provide the newborn with maximal disease resistance. We investigated the appearance of IgG in mammary pre- and post partum secretions in cows without a dry period (continuously milked, Dry0) and compared the secretions with cows that experienced a dry period of 60 d (Dry60). Blood was collected during the experimental period and plasma analysed for progesterone (P4) and prolactin (Prl). Approximately −6 d relative to parturition, the Dry0 animals exhibited increased concentration of IgG in their secretions to an average of ∼35 mg/ml that remained rather constant through subsequent pregnancy and following parturition. Dry0 cows were producing an average IgG concentration in parturition colostrum of 44·2±17·6 mg/ml that was not different than that of controls (66·86±16·8 mg/ml). However, Dry0 cows exhibited high variation, different peak times (day) of IgG concentration including times that occurred both pre and post parturition. IgG mass of the Dry0 cows remained rather constant pre- and post partum and did not show the same declining mass following parturition that was shown for the Dry60 cows. The change in plasma P4 and Prl were shown to have no timing effect on colostrum IgG concentration.